Waarom die vorm en oriëntatie van Borssele? Herkomst en betekenis van een Zeeuwse dorpsplattegrond uit de vroege zeventiende eeuw - van der Weele, Pieter; Rutte, Reinout (Bulletin KNOB, 2021)
The village of Borssele was founded in 1616 in a polder of the same name on the island of Zuid-Beveland in the province of Zeeland. The driving force behind both the diking of the polder and the construction of the village during the Twelve Year Truce (1609-1621) in the young Dutch Republic was the mayor of the city of Goes, Cornelis Soetwater. This article argues that the unusual form and orientation of the Borssele village plan reflects a conscious decision by Soetwater to combine and improve on the best of the Zeeland’s impoldering and village planning tradition, and on the most striking old Zuid-Beveland villages. Soetwater’s decision to give Borssele’s main square a resolutely northern orientation and an unconventional, rotated positioning within the polder grid, and to model its plan on that of the most distinctive medieval villages on the islands of Zuid-Beveland, Nisse and Kloetinge, served to anchor the new village emphatically in its immediate surroundings. Moreover, Borssele represents the culmination of an honourable tradition initiated during the fifteenth century by the Zeeland nobleman Adriaan van Borssele with the construction of ringstraatdorpen[1] such as Dirksland, Sommelsdijk and Middelharnis, in the large Flakkee polders. The marquises of Bergen op Zoom and the family of Orange continued this tradition during the sixteenth century in the construction of Willemstad and Colijnsplaat, among others. Soetwater exploited the symbolic significance of these new villages, which was as important to Adriaan van Borssele and his followers as their economic and administrative function, for his own purposes. By continuing a trend towards orthogonality and symmetry in the layout of sixteenth-century ringstraatdorpen in the double symmetry of the Borssele street plan, Soetwater was able to emphasize the victory of rationality over chaos. Not just in the sense that the wild water had been turned into orderly cultural landscape, but also in the sense that after many years of war, the Twelve Year Truce had ushered in a period of peace, order and the prospect of a bright future. [1] The ringstraatdorp was a combination of two older types of Zeeland village plans, the kerkringdorp and the voorstraatdorp. Its main street (voorstraat) was perpendicular to the polder dike and its landward end terminated in a kerkring (church encircled by a street).